Current Controlled AC/DC Converter and Its Performance—A Mathematical Model - Jan Iwaszkiewicz; Piotr Mysiak; Adam Muc (Energies)
This paper describes a mathematical model of the AC/DC converter. The analytic expressions define fundamental physical variables of the converter and their relations: phase current and voltage, shift angle between these quantities, power factor, and supply voltage UD. The mains voltage is defined as a digitalized sine wave while the current’s wave takes the form of a line segment defined in an appropriate time interval. The model permits the description of two modes of operation: inverter and rectifier. The assumed control method of the converter depends on the successive switching of selected vectors. They are qualified according to the principle of the lowest error between the reference and measured phase current value. The control method is realized by using hysteresis algorithms. Five different algorithm solutions and comparative results are implemented. Several examples of current, voltage, and vectors taken during the simulation and experimental works are executed.